2020
DOI: 10.1029/2020jg005799
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Perspectives to Understand Lake Ice Dynamics in a Changing World

Abstract: Ice cover plays a critical role in physical, biogeochemical, and ecological processes in lakes. Despite its importance, winter limnology remains relatively understudied. Here, we provide a primer on the predominant drivers of freshwater lake ice cover and the current methodologies used to study lake ice, including in situ and remote sensing observations, physical based models, and experiments. We highlight opportunities for future research by integrating these four disciplines to address key knowledge gaps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 160 publications
(225 reference statements)
4
53
0
Order By: Relevance
“…Larger, deeper lakes require colder air temperatures to freeze and take longer to cool in the fall. In addition, lakes with longer fetches are more likely to lose the initial skim of ice through increased wind action and are additionally sensitive to experiencing an ice‐free year (Sharma et al., 2019, 2020; Woolway et al., 2020). For example, we found that the ice‐free threshold for deeper and larger lakes, such as Lake Champlain and Grand Traverse Bay, Lake Michigan was below −5 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Larger, deeper lakes require colder air temperatures to freeze and take longer to cool in the fall. In addition, lakes with longer fetches are more likely to lose the initial skim of ice through increased wind action and are additionally sensitive to experiencing an ice‐free year (Sharma et al., 2019, 2020; Woolway et al., 2020). For example, we found that the ice‐free threshold for deeper and larger lakes, such as Lake Champlain and Grand Traverse Bay, Lake Michigan was below −5 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Warming spring water temperatures and increases in the length of the frost-free season can prolong annual growing seasons for aquatic organisms through warmer summers, longer and warmer autumns, and shorter ice-cover duration (Sharma et al, 2019, 2020). Temperature is an abiotic master factor for aquatic ecosystems because water temperature directly affects the physical and chemical properties of water, and phenology, reproductive events, metabolic rates, growth, and survival of aquatic organisms (Fry, 1964; Brett, 1979; Gillooly et al, 2002; Brown et al, 2004; Ohlberger et al, 2007; Busch et al, 2012; Cline et al, 2013; Little et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the passive microwave sensors have coarse spatial resolutions (typically ranging from 6.25 km to 25 km), hence limiting their effectiveness within heterogeneous landscapes [15]. Therefore, other remote sensing data types with higher spatial resolutions, including synthetic aperture radar (SAR) [7,22], optical imagery [8,9,23,24], and UAV [25], have also been used for mapping lake ice-off phenology.…”
Section: Introductionmentioning
confidence: 99%
“…These errors on the temporal dimension could undermine or even lead to the failure of the BUE identification. In this study, we used ERA5 Ta data for outlier removal because the lake ice melting is highly correlated to the warming process of air temperature [9,25,40]. Due to the spatial resolution mismatch, the bicubic interpolation algorithm [41] was used for resizing the original ERA5 Ta data to 20 m, and the 28-day average air temperature (Ta 28 ) was adopted as the metric to correct unreasonable ice or water presence [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation